2015
DOI: 10.1590/s1517-838246320140180
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant capacity of several Iranian, wild and cultivated strains of the button mushroom

Abstract: The white button mushroom, Agaricus bisporus, is the most commonly grown mushroom in Iran; however, there is a significant shortage of research on its antioxidant activity and other medicinal properties. The aim of this study was to evaluate antioxidant capacity of the methanolic extracts from four cultivated strains and four Internal Transcribed Spacer (ITS)-identified, Iranian wild isolates of A. bisporus. Evaluations were made for total phenols, flavonoids and anthocyanins, and 2, 2-diphenyl-1-picrylhydrazy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 19 publications
(30 reference statements)
0
6
1
Order By: Relevance
“…3.5 mg/g DW, and 4.83 mg/g DW, respectively. In their investigations of wild and cultivated white button mushrooms, Tajalli et al (2015) showed a wide variation in the content of phenolic compounds ranging from 3.61 to 9.61 mg GAE/g DW. The values obtained in studies conducted by other authors are also substantially higher, i.e.…”
Section: Total Phenolic Contents and Antioxidant Activitiesmentioning
confidence: 99%
“…3.5 mg/g DW, and 4.83 mg/g DW, respectively. In their investigations of wild and cultivated white button mushrooms, Tajalli et al (2015) showed a wide variation in the content of phenolic compounds ranging from 3.61 to 9.61 mg GAE/g DW. The values obtained in studies conducted by other authors are also substantially higher, i.e.…”
Section: Total Phenolic Contents and Antioxidant Activitiesmentioning
confidence: 99%
“…Turfan et al (2018) found that total phenolic concentration of mushrooms varied between 28.68 and 157.39 mg DW -1 . Results of Tajalli et al (2015) showed that the amount of total phenolic and anthocyanin ranged from 3.61 to 9.61 mg g -1 and from 0.087 mg 100 g -1 to 7.70 mg 100 g -1 respectively in six wild edible mushrooms. Hussein et al (2015) determined that total phenolic level changed between 136.21 mg 100 g -1 and 431.03 mg 100 g -1 in seven wild edible mushrooms.…”
Section: Resultsmentioning
confidence: 99%
“…It was previously reported that the wild state of the plant is usually in a shady and moist habitat but the cultivated plant may be inconsistently shaded and other environmental conditions may not be adequately simulated unlike the ones in the wild; hence there may be phytochemical variations [31] as shown in the results of this research. According to Ashashri et al [33] and Tajalli et al [34], the exposure of plants to harsh environmental conditions including insects and infections is known to enhance the productions of flavonols and flavonoids. These phytochemicals are for self-protection.…”
Section: Discussionmentioning
confidence: 99%